2018
DOI: 10.1175/jcli-d-17-0439.1
|View full text |Cite
|
Sign up to set email alerts
|

A PDRMIP Multimodel Study on the Impacts of Regional Aerosol Forcings on Global and Regional Precipitation

Abstract: Atmospheric aerosols such as sulfate and black carbon (BC) generate inhomogeneous radiative forcing and can affect precipitation in distinct ways compared to greenhouse gases (GHGs). Their regional effects on the atmospheric energy budget and circulation can be important for understanding and predicting global and regional precipitation changes, which act on top of the background GHG-induced hydrological changes. Under the framework of the Precipitation Driver Response Model Intercomparison Project (PDRMIP), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(138 citation statements)
references
References 78 publications
9
111
1
1
Order By: Relevance
“…In other words, the precipitation trends during the past 110 years in the Mediterranean are likely to be only weakly sensitive to scattering aerosols that were not modeled (e.g., organic carbon, nitrate) or the uncertainties in aerosol negative forcing (probably not even for indirect forcing, as they were included in sulfate simulations for most models). The small sensitivity of SO 4 is likely due to compensation between local and remote effects (Liu et al, 2018). Combined with its small ERF, the role of SO 4 appears to be negligible during this period.…”
Section: Case Study -Historical Observations and Scaled Model Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In other words, the precipitation trends during the past 110 years in the Mediterranean are likely to be only weakly sensitive to scattering aerosols that were not modeled (e.g., organic carbon, nitrate) or the uncertainties in aerosol negative forcing (probably not even for indirect forcing, as they were included in sulfate simulations for most models). The small sensitivity of SO 4 is likely due to compensation between local and remote effects (Liu et al, 2018). Combined with its small ERF, the role of SO 4 appears to be negligible during this period.…”
Section: Case Study -Historical Observations and Scaled Model Resultsmentioning
confidence: 92%
“…Hence this study focuses on aspects of the response that appear to be less sensitive to those interactions as they are relatively robust across the models (despite some emission-driven models using interactive aerosols while others used climatological fields). Many PDRMIP studies have taken this approach Myhre et al, 2017;Stjern et al, 2017;Liu et al, 2018;Richardson et al, 2018), though further work with models incorporating more realistic aerosol-cloud in-teractions would of course be valuable in determining the veracity of all conclusions from the project.…”
Section: Datamentioning
confidence: 99%
“…The greater impact of European emissions is likely due to factors connected with the nearer proximity of Europe to the Arctic but may also be related to a saturation of aerosol‐cloud interactions over East Asia, as well as a greater climatological cloud cover, which could mask the direct aerosol forcing in that region (Kasoar et al, ). In another PDRMIP analysis, Liu et al () also found that the forcing from European SO 4 increases had a stronger efficacy in terms of global temperatures and precipitation effects than that from the Asian region. In the present study, we find that the concentration‐based models do not show this difference, at least in the Arctic.…”
Section: Arctic Responses To Regional Perturbationsmentioning
confidence: 95%
“…The Precipitation Driver Response Model Intercomparison Project (PDRMIP) (Myhre et al, ) provides a unique data set that allows for investigations into climate responses to separate and clearly defined climate drivers, such as greenhouse gases or aerosols, in a multimodel framework. This has led the way for several studies that have investigated various aspects of climate driver‐response relationships from a global perspective (Liu et al, ; Samset et al, ; Samset et al, ; Stjern et al, ). Here we use the PDRMIP data set to analyze the climate response in the Arctic (defined as the region north of 60°N).…”
Section: Introductionmentioning
confidence: 99%
“…The ITCZ shifts toward a warmer hemisphere in all ocean basins regardless of the spatial pattern of surface heating anomalies, whether an external forcing is spread over the entire North Atlantic region or concentrated in a narrow region along the Gulf Stream (L'Hévéder et al, 2015). Sulfate aerosols over Asia leads the ITCZ to shift southward across the Pacific, Atlantic, and Indian Ocean basins (Liu et al, 2018). Sulfate aerosols over Asia leads the ITCZ to shift southward across the Pacific, Atlantic, and Indian Ocean basins (Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%